Do All Jazz Musicians Wear Berets? - Rowan, Brent (Critical Studies in Improvisation / Études critiques en improvisation, 2025)
Brent Rowan reflects on his relationship with Ajay Heble, recalling the many ways their lives have crossed paths in Guelph.